Effect of an Aerobic Exercise Program on Fetal Growth in Pregnant Women - A Khaledan; Sh Mirdar; NS Motahari Tabari; M Ahmad Shirvani (حیات, 2010)
Background & Aim: Exercise is an integral component of physical and mental health. Attention to exercise in women, regarding their physiologic situation is essential. This study aimed to investigate the effect of a specific aerobic exercise program on fetal growth in pregnant women.Methods & Materials: In this clinical trial, 39 pregnant women in 24-32 weeks of gestation were enrolled. The participants were randomly allocated to experimental (n=18) and control (n=21) groups. Women with single pregnancies and intact amniotic membranes were included. Women who had any contraindications for exercise were excluded from the study. Exercise program included stretching and flexibility exercise and aerobic exercise (constant walking for 30-45 minuets) three days a week for eight weeks. Data were analyzed using descriptive statistics, c2, t-test, Kolmogro-smirnov and repeated measurements. P<0.05 was considered to be significant.Results: The results showed a 1.37% increase in the newborns;apos weight in the intervention group however, the difference was not statistically significant. The average of head circumference and newborns;apos length in the intervention group;aposs newborns were 0.21cm and 0.09cm more than the control group;aposs newborns, respectively. These differences were not statistically significant too (P>0.05).Conclusion: There were no reductions in the growth of the fetuses following the exercise activities. This kind of exercise has no adverse effect on fetal growth.